Mechanism of antiglycating properties of syringic and chlorogenic acids in in vitro glycation system. (November 2015) - Bhattacherjee, Abhishek; Datta, Abhijit
Abstract: Glycation is known to be related with several pathophysiological complications. Several chemical and natural compounds had been tested on different systems to prevent glycation-related complications. Though they show a promising result initially, but often fail to succeed in preclinical trials. In this paper, we try to demonstrate how syringic and chlorogenic acids, two largely consumed natural products bind with BSA to prevent glycation-associated complications. Biochemical (glucose estimation) and biophysical (CD, MALDI, MS/MS) techniques have been used to demonstrate the antiglycating mechanism. We have calculated binding constant 3.07 ± 0.42 × 10 − 4 and 2.67 ± 0.28 × 10 − 4 M − 1 for syringic and chlorogenic acids respectively. Further we have successfully purified BSA–phenolic acid conjugates by chromatographic methods. Molecular modeling and mass spectrometric studies suggested that Lys 93, 261, 232, Arg 194 and Lys 93, Arg 194 are the responsible binding residues for syringic and chlorogenic acids respectively. Highlights: Syringic and chlorogenic acid are two important phenolics found in several fruits. Binding properties and binding efficacy of these molecules are not known. We have determined binding sites of these molecules by Mass Spectrometry. Try to explain the molecular mechanism of their antiglycating properties.